Investigating the use of Mondrian Art Puzzles to develop students’ problem-solving and mindset - Damayanti, Alfiyana; Nurhasanah, Farida (International Journal on Education Insight, 2024)
Indonesia is currently undergoing changes towards the era of society 5.0 after passing through the 4.0 revolution. In the face of such changes in a short time, it is important for human resources to have 21st century skills or 4Cs such as critical thinking and problem solving, creativity and innovation, communication, and collaboration. Therefore, along with the development of education that is increasingly complex, problem-solving skills and students' mindset are crucial aspects that need to be developed in the learning process of Mathematics. Therefore, this study investigates the effectiveness of Mondrian Art Puzzle as an innovative learning stimulus with the aim of influencing problem-solving ability and mindset development. In this quantitative research study, data were collected through tests and questionnaires in both experimental classes. The first class used Mondrian Cube (apps) and Mondrian Paintings (handout), while the second class only used Mondrian Cube. The findings show that the combination of Mondrian Cube and Mondrian Paintings is more effective in improving mathematical problem-solving skills than Mondrian Cube alone. Although not statistically significant, Mondrian Art Puzzles has the potential to encourage the development of mindset by reducing fixed mindset students and increasing growth mindset students, thus having a positive impact on learning mathematics.